Tetrahydrobiopterin deficiency in the pathogenesis of Fabry disease. (2nd February 2017) - Shen, Jin-Song; Arning, Erland; West, Michael L.; Day, Taniqua S.; Chen, Shuyuan; Meng, Xing-Li; Forni, Sabrina; McNeill, Nathan; Goker-Alpan, Ozlem; Wang, Xuan; Ashcraft, Paula; Moore, David F.; et al.
Abstract: Fabry disease is caused by deficient activity of α-galactosidase A and subsequent accumulation of glycosphingolipids (mainly globotriaosylceramide, Gb3 ), leading to multisystem organ dysfunction. Oxidative stress and nitric oxide synthase (NOS) uncoupling are thought to contribute to Fabry cardiovascular diseases. We hypothesized that decreased tetrahydrobiopterin (BH4) plays a role in the pathogenesis of Fabry disease. We found that BH4 was decreased in the heart and kidney but not in the liver and aorta of Fabry mice. BH4 was also decreased in the plasma of female Fabry patients, which was not corrected by enzyme replacement therapy (ERT). Gb3 levels were inversely correlated with BH4 levels in animal tissues and cultured patient cells. To investigate the role of BH4 deficiency in disease phenotypes, 12-month-old Fabry mice were treated with gene transfer-mediated ERT or substrate reduction therapy (SRT) for 6 months. In the Fabry mice receiving SRT but not ERT, BH4 deficiency was restored, concomitant with ameliorated cardiac and renal hypertrophy. Additionally, glutathione levels were decreased in Fabry mouse tissues in a sex-dependent manner. Renal BH4 levels were closely correlated with glutathione levels and inversely correlated with cardiac and kidney weight. In conclusion, this study showed that BH4 deficiency occurs in Fabry disease and may contribute to the pathogenesis of the disease through oxidative stress associated with a reduced antioxidant capacity of cells and NOS uncoupling. This study also suggested dissimilar efficacy of ERT and SRT in correcting pre-existing pathologies in Fabry disease.